Retrobulbar pain in isolated sphenoiditis - Arustamyan, I. G.; Karpischenko, S. A.; Stancheva, O. A.; Kucheryavenko, M. N.; Nersesyan, M. V.; Kaplun, D. I.; Shpakouskaya, I. I. (Medicinskij sovet, 2025)
Introduction . The opacification of the unilateral sphenoidal sinus (USS) in computed tomography is caused by various diseases, including inflammation and infectious sinusitis, benign and malignant tumors and encephalocles. Symptoms of isolated lesions of this sinus are varied and nonspecific. This symptom includes retrobulbar pain, which does not occur with other paranasal spasms. This makes this symptom diagnostically valuable. Aim . Тo consider the relationship between the presence of retrobulbar pain in patients with isolated sphenoiditis and the nature of pathological changes in the sinus. Materials and methods . A retrospective cohort study of multiple institutions was conducted on all patients with USS from 2017 to 2024. The demographics of the patients, symptoms, findings of nasal endoscopy and CT scans were recorded. For categorical features, the obtained data were analyzed using statistical methods. Results . Based on the analysis, it was found that retroorbital pain was more often detected in patients with fungal formation of the sphenoid sinus in the association with or without purulent fundus (p = 0.01), and was also more often observed in client patients. Moreover, no correlation was observed between diplopia and inflammatory pathology. Conclusion . Thus, retroorbital pain is a predictor of sinus chronic inflammation, requiring surgical intervention in short time, pathological changes in the sinus.